Teicoplanin and Meropenem Prophylaxis in Open Heart Surgery- Efficacy and Safety (Cardiovascular Journal, 2017)
Background: Prophylactic efficiencies of teicoplanin and meropenem against infections in open heart surgery were investigated in a retrospective observational study.Method: In new regime of antibiotics single dose of teicoplanin and 72 hours coverage with meropenem were used in open heart surgery. One dose of teicoplanin was administered during induction of general anesthesia. First dose of meropenem was administered during induction of general anesthesia, and then 8 to 12 hourly continued up to 72 hours. This regime of antibiotics was compared retrospectively with previous regime of antibiotics containing flucloxacillin, ceftriaxone and gentamycin continuing from induction of general anesthesia up to 5th post operative day.Results: In 203 patients receiving new regime containing teicoplanin and meropenem, there was no infection and there was no nephrotoxicity. But in 101 patients receiving conventional regime containing flucloxacillin cefriaxone and gentamycin, there were 21 patients (21%) with surgical site infections; among them 3 patients expired, and nephrotoxicity developed in 15(14.85%) patients.Conclusion: As prophylactic agent combination of teicoplanin and meropenem may be more effective and safer against infection in open heart surgery.Cardiovasc. j. 2017; 10(1): 63-67